The New Testament in the Original Greek - Westcott, Brooke Foss 1825-1901; Hort, Fenton John Anthony 1828-1892 (Cambridge Cambridge University Press, 2010)
The publication in 1881 of The New Testament in the Original Greek, by the Cambridge scholars Brooke Foss Westcott (1825–1901) and Fenton John Anthony Hort (1828–92), marked the culmination of twenty-eight years of work and revolutionised the theory and methods of New Testament textual criticism. The editors broke with tradition and reconstructed a critical text based on the third-century uncial manuscripts Codex Vaticanus and Codex Sinaiticus, paving the way for future editions. Westcott and Hort's claim to reconstruct the 'original text' may seem extravagant today; but according to Bruce Metzger theirs was the 'most noteworthy critical edition of the Greek Testament ever produced by British scholarship'.
Originally published in Cambridge by Macmillan in 1881. - Title from publisher's bibliographic system (viewed on 06 Jun 2016)
Keywords: Bible; Bible ; New Testament ; Greek